Air quality and human health impacts of grasslands and shrublands in the United States. (June 2018) - Gopalakrishnan, Varsha; Hirabayashi, Satoshi; Ziv, Guy; Bakshi, Bhavik R.
Abstract: Vegetation including canopy, grasslands, and shrublands can directly sequester pollutants onto the plant surface, resulting in an improvement in air quality. Until now, several studies have estimated the pollution removal capacity of canopy cover at the level of a county, but no such work exists for grasslands and shrublands. This work quantifies the air pollution removal capacity of grasslands and shrublands at the county-level in the United States and estimates the human health benefits associated with pollution removal using the i-Tree Eco model. Sequestration of pollutants is estimated based on the Leaf Area Index (LAI) obtained from the Moderate Resolution Imaging Spectroradiometer (MODIS) derived dataset estimates of LAI and the percentage land cover obtained from the National Land Cover Database (NLCD) for the year 2010. Calculation of pollution removal capacity using local environmental data indicates that grasslands and shrublands remove a total of 6.42 million tonnes of air pollutants in the United States and the associated monetary benefits total $268 million. Human health impacts and associated monetary value due to pollution removal was observed to be significantly high in urban areas indicating that grasslands and shrublands are equally critical as canopy in improving air quality and human health in urban regions. Graphical abstract: Image 1 Highlights: First spatial inventory of air pollution removal by grasslands and shrublands in conterminous US and DC. Air pollution removal were substantially larger in rural areas than in urban areas. Pollutant removal by grasslands occurred predominantly in the Great Plains area. Grasslands and shrublands are equally critical as trees in improving air quality and human health in urban areas. Monetary value associated with human health effects is valued at millions of dollars annually.